The influence of Omnichannel Shopping Experience on Customer Citizenship Behavior through Customer Engagement (Survei on Customers of Local Sportswear Brand Industry) - Permana, Hadi; Wibowo, Lili Adi; Lisnawati, Lisnawati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2025)
This study aims to analyze the effect of omnichannel shopping experience on customer citizenship behavior through customer engagement in the local sportswear brand industry in Indonesia. The research background is based on the phenomenon of increasing competition in the sportswear industry driven by changes in consumer behavior, market globalization, and digital technology development. The omnichannel shopping experience is seen as a strategy that can provide a consistent shopping experience across various channels, while customer engagement is a key factor in shaping voluntary customer behaviors that benefit the company. This study employs a quantitative approach with a survey method targeting consumers of local sportswear brands such as 910, Specs, Mills, and Ortuseight. Data were analyzed using Structural Equation Modeling (SEM) to examine the direct and indirect relationships among variables. The results show that the omnichannel shopping experience has a significant positive effect on customer engagement, and both together positively influence the increase in customer citizenship behavior. These findings provide strategic implications for companies to optimize omnichannel-based marketing strategies and enhance customer engagement to build long-term brand loyalty and advocacy.